Building Security - Sjolund, Olof (Sweden, 2004)
Film about a peace camp created mainly by Israeli and Palestinians peace-activists, but also by people of other nationalities, as a form of protest against the building of the Security Wall. The main argument is that this wall works against peace and security and it will also produce more impovrished and frustrated people, as it breaches their lands and their means of communication and of living. Their immediate aim is to save the land and house of a Palestinian family. The director makes a direct comparison with the Berlin Wall, anticipating similar negative, destructive effects with the one built by the state of Israel.
Duration: 00:35:00
Keywords: Documentary films